2009
DOI: 10.1016/j.bbr.2008.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned lick behavior and evoked responses using whisker twitches in head restrained rats

Abstract: To examine whisker barrel evoked response potentials in chronically implanted rats during behavioral learning with very fast response times, rats must be calm while immobilized with their head restrained. We quantified their behaviors during training with an ethogram and measured each individual animals' progress over the training period. Once calm under restraint, rats were conditioned to differentiate between a reward and control whisker twitch, then provide a lick response when presented with the correct st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…The rigid restraint chamber has restricted space so movement by the animal can cause unwanted tension on the head stage by twisting of the recording cables if the head is not fixed. Our studies previously tested different methods of restraint and found the wrap to be the most comfortable method, exhibiting fewer bad behaviors [56]. Head fixation has many advantages including the ability to perform precisely timed whisker stimulation that is time-locked to an event such as licking and recording the neuronal activity related to this behavior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rigid restraint chamber has restricted space so movement by the animal can cause unwanted tension on the head stage by twisting of the recording cables if the head is not fixed. Our studies previously tested different methods of restraint and found the wrap to be the most comfortable method, exhibiting fewer bad behaviors [56]. Head fixation has many advantages including the ability to perform precisely timed whisker stimulation that is time-locked to an event such as licking and recording the neuronal activity related to this behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Food and/or fluid deprivation is a common laboratory procedure used to increase motivation for obtaining a reward [8, 12, 13, 19, 24, 56]. However, dietary restriction has several physiological and neurobehavioral effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other methods that tend to introduce stressful conditions that result in discomfort over long periods of time, the restraining mechanism using a hammock and jacket allows the rats to make slight adjustments in body position if necessary for comfort while providing adequate restraint still. Many studies 21 involving awake, nonanethetized, and head-restrained rats have applied this approach and proved that the rats remained calm and exhibited fewer bad behaviors during the prolonged experiment.…”
Section: Discussionmentioning
confidence: 99%
“…We implemented a restraining mechanism that allowed for the highest level of comfort possible 21 , since the rat stayed awake during the relatively long time recording in the seizure experiment. For restraint, we used both hammocks and straight-jacket type wraps to better fit our needs.…”
Section: Methodsmentioning
confidence: 99%